Prognostic markers of lymphoma development in primary Sjögren syndrome. (July 2019) - Retamozo, S; Brito-Zerón, P; Ramos-Casals, M
Sjögren syndrome is a systemic autoimmune disease that principally affects women between the fourth and sixth decades of life who present with sicca symptomatology caused by dryness of the main mucosal surfaces. The clinical spectrum of Sjögren syndrome extends from dryness to systemic involvement. Since 1978, Sjögren syndrome has been closely associated with an enhanced risk of lymphoma, one of the most severe complications a patient may develop. Primary Sjögren syndrome patients have a 10–44-fold greater risk of lymphoma than healthy individuals, higher than that reported for systemic lupus erythematosus and rheumatoid arthritis. The close link between lymphoma and Sjögren syndrome is clearly exemplified by the very specific type of lymphoma arising in Sjögren syndrome patients, mainly low-grade B-cell lymphomas (predominantly a marginal zone histological type) with primary extranodal involvement of the major salivary glands (overwhelmingly parotid), with a primordial role of cryoglobulinemic-related markers (both clinical and immunological). The most recent studies support a higher number of risk factors detected in an individual leads to a higher lymphoma risk. A close follow-up of high-risk groups with longitudinal assessments of all known risk factors, including cryoglobulin-related markers and EULAR Sjögren's syndrome disease activity index measurement in particular, is mandatory.